Hiperglucemia como factor pronóstico de mortalidad en pacientes hospitalizados por Covid-19 del Hospital Isidro Ayora Loja - Tapia Elizalde, Carlos Andrés (2023)
The understanding of COVID-19 is evolving, and a number of factors are now known or are being studied that contribute to greater severity of the clinical picture, including higher mortality; one of these factors is hyperglycemia. The purpose of the study was to determine whether hyperglycemia upon admission in patients without a diagnosis of diabetes to the emergency area influences the prognosis of mortality. In patients hospitalized with COVID19 at the Isidro Ayora Loja Hospital and as specific objectives: Estimate the prevalence of hyperglycemia, characterize the population by age and sex variables, laboratory tests (glycemia value), determine hospital stay, outcome and the association between hyperglycemia and mortality in patients hospitalized with COVID-19 at the Isidro Ayora Hospital, A retrospective analytical observational study was carried out with a sample of 162 patients diagnosed with COVID-19 during the period March 2020 to September 2020. According to the results obtained: the prevalence of hyperglycemia is 65.4% (n=106), the majority of COVID-19 cases occurred in people over 60 years of age with 60.5% (n=98) and 67.9% (n=110) were male, the most prevalent clinical condition was moderate cases 79.0% (n=128). Mortality was higher in patients with glycemic levels at admission > 180 mg/dl with 70.0% (n=35). Regarding glucose levels ≥140 and <180 mg/dl or <140 mg/dl, the mortality rate was 55.4% (n=31) and 32.1% (n=18) respectively. With a statistically significant p value p <0.001. When adjusting the variables, hyperglycemia is an independent risk factor for mortality: 1.1 (95% CI 1.04-1.32) and 2.1 (95% CI 1.1-1.45) times higher risk of death in blood glucose levels of 140-180 mg/dl and >180 mg/dl, respectively. Thus, hyperglycemia >140 mg/dl upon admission in non-diabetic patients to the area of emergency is an independent predictor of mortality